A rare case of isolated hydatid cyst of breast. (2015) - kumar, Amit; Kumar, Amar; Gaurav, Kumar; Chandra, Gautam; Tiwary, A.K.; Bhagat, S.; Sarawgi, M.
Highlights: Hydatid cyst of the breast is very rare. It is challenging to differentiate it from other tumoral lesions of the breast as it might mimic fibroadenoma, phyllodes tumors, chronic abscesses or even carcinoma. Only few reports of breast hydatid cyst are published and majority of the reported cases have been diagnosed postoperatively as it is not possible to reach definitive diagnosis with clinical examination and radiological investigations only. In spite of being very uncommon, it should be included in differential diagnosis of breast lumps for patients living in endemic areas. Surgical excision of the cyst is the treatment of choice. Abstract: Introduction: Hydatid cyst of the breast is very rare. It is challenging to differentiate it from other tumoral lesions of the breast. Only few reports of breast hydatid cyst are published and majority of the reported cases have been diagnosed postoperatively as it is not possible to reach definitive diagnosis with clinical examination and radiological investigations only. Presentation of case: A 31-year old woman presented with a painless lump in the right breast since one year duration. On clinical examination, a non-mobile, firm lump was detected in the right breast associated with nipple retraction, but there was no axillary lymphadenopathy. This case was diagnosed as hydatid cyst incidentally during surgery from its gross appearance which mimics that of a liver hydatid cyst, normally common in this endemic area. Discussion: Hydatid disease is a parasitic infection caused by the larval form of Echinococcus granulosus and seen endemically among sheep-raising communities. The breast can be a primary site or part of a disseminated hydatidosis. It might mimic fibroadenoma, phyllodes tumors, chronic abscesses, or even carcinoma. Preoperative diagnosis can be made by fine needle aspiration cytology. It also can be diagnosed by radiological or serologic means but neither of them is definitive. Surgery is the treatment of choice. Conclusion: Hydatid cyst of the breast is very uncommon but it should be included in differential diagnosis of breast lumps for patients living in endemic areas.